Independent Evaluation of IFC’s Development Results 2009 : Knowledge for Private Sector Development - World Bank (Washington, DC, 2012)
The independent evaluation of International Finance Corporation's (IFC's) development results 2009 assesses the development outcomes and additionality (unique role and contribution) of IFC interventions. It analyzes factors driving results, and reviews performance patterns on a thematic topic. This year's thematic is IFC's Advisory Services (AS), knowledge services that IFC provides to either private companies or governments in support of private sector development. To enhance development impact, the report recommends that IFC: i) effectively manage the tension between protecting the portfolio and responding to opportunities during crisis; ii) set out an overall strategy for IFC advisory services, addressing the need for a clear vision and business framework and more closely linked with IFC's global corporate strategy; iii) pursue more programmatic AS interventions; iv) improve execution of the AS pricing policy; and v) strengthen AS performance measurement and internal knowledge management.